Dysprosium complex with 1,10-phenanthroline-5,6-dione: Synthesis, structure, DNA binding profile, and in vitro cytotoxic evaluation against HT29 cancer cell lines - Tilehkan, Ali; Arvand, Majid (Polyhedron, 2025)
This study provides valuable insights into the interaction mechanism of the Dy(phen-dion)3 complex with DNA, highlighting the potential of this novel complex for antitumor therapies. Additionally, these findings contribute to the design of new and efficient pharmaceutical molecules. [Display omitted] The study investigates the interactions between a dysprosium(III) complex containing 1,10-phenanthroline-5,6-dione (Dy(phen-dion)3) and deoxyribonucleic acid (DNA), utilizing a range of analytical techniques. These methods include cyclic voltammetry (CV), UV–Vis spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, electrophoresis, fluorescence spectrophotometry, and molecular docking calculations. The findings reveal compelling evidence of significant binding between Dy(phen-dion)3 and DNA. The binding affinity of Dy(phen-dion)3 to DNA was quantified, yielding a high binding constant (Kb) of 3 × 105 M−1. Additionally, fluorescence resonance energy transfer experiments indicated efficient energy transfer between DNA as the donor and Dy(phen-dion)3 as the acceptor, suggesting close proximity between the two entities. The quenching constant (KSV) obtained for this complex was 1.94 × 10−3 M−1. Electrochemical measurements suggest a groove-binding mode for the complex with DNA, characterized by a 1:1 binding ratio. The interaction is likely facilitated by hydrogen bonding and van der Waals forces, which play crucial roles in stabilizing the complex. Moreover, the in vitro antitumor activity of Dy(phen-dion)3 was assessed using the MTT assay on HT29 cells. The results showed that with the increase in the concentration of Dy(phen-dion)3, the resistance of HT29 cancer cells to the anticancer drug methotrexate (MTX) increased at a concentration of 10.16 μg mL−1, highlighting the potential of the complex as an effective therapeutic agent in the treatment of colorectal cancer.